(untitled) (Journal of Pharma Insights and Research, 2026)
Nosocomial infections contribute to the complexity of critical care, leading to substantial increases in patient morbidity, mortality, and healthcare expenditure. The intensive care unit (ICU) serves as a reservoir for highly virulent and multidrug-resistant (MDR) organisms, a phenomenon caused by the frequent use of invasive medical devices, the physiological vulnerability of critically ill patients, and the selective pressure exerted by broad-spectrum antimicrobial therapy. Gram-negative bacilli, particularly Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa, dominate the microbiological environment of the ICU, frequently manifesting as ventilator-associated pneumonia and bloodstream infections. Simultaneously, Gram-positive pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) remain persistent threats. The evolution of resistance is characterized by the production of extended-spectrum beta-lactamases (ESBLs), carbapenemases, and the formation of robust biofilms, which collectively render conventional therapeutic regimens ineffective. High rates of carbapenem resistance among Enterobacteriaceae and non-fermenting bacilli requires the use of last-resort antibiotics, further narrowing the window for successful clinical intervention. Effective management relies on the implementation of stringent infection control procedures, strong antimicrobial stewardship, and continuous local epidemiological surveillance. Solving the rising concern of antimicrobial resistance requires a shift toward precision diagnostics and novel therapeutic regimens to reduce the impact of healthcare-associated infections in the most vulnerable patient populations